Adoption of Climate Resilient Cropping Patterns in Southern Coastal Region of Bangladesh: Farmer’s’ Perception (SAARC Journal of Agriculture, 2021)
The study was carried out in Batiaghata upazila of Khulna district to identify different climate resilient cropping patterns that had been practiced over the past three decades as well as the farmers’ perception about the causes of adopting climate resilient cropping patterns. Information was collected through personal interview, focus group discussion, systematic study of available records and browsing internet. A slight change was observed regarding climate resilient cropping pattern over the last 30 years in the study area. About 30 years ago, five cropping patterns were practiced, only one pattern (Fallow-Fallow-T. Aman) was found climate resilient. About 20 years ago, 11 cropping patterns were practiced, 5 patterns (Fallow-Fallow- T. Aman, Boro-Fallow-T. Aman, Boro-Gher (vegetables)-T. Aman, Boro-Gher (vegetables)-Fallow and Fallow-Gher (vegetables)-T. Aman) were found climate resilient. About 10 years ago, 11 cropping patterns were practiced, 7 patterns (Sesame-Fallow-T. Aman, Boro- Fallow-T. Aman, Boro-Gher (vegetables)-Fallow, Fallow-Fallow- T.Aman, Boro-Jute-T. Aman, Boro-Gher (vegetables)-T. Aman and Fallow-Gher (vegetables)-T. Aman) were found climate resilient. At present, 14 cropping patterns are being practiced. Out of which, six patterns are climate resilient. Respondents justified nine causes for adopting climate resilient cropping patterns, while increase in cropping intensity was the most significant, while lower input cost was least significant. Most of the respondents (93.80%) had highly clear perception and the rest (6.20%) had moderately clear perception. A positive relationship of education and mass media exposure was observed with their perception.SAARC J. Agri., 18(2): 207-217 (2020)